PERKEMBANGAN SAINS DAN ISLAM BAGI KEHIDUPAN MANUSIA - Berliana Nur Annisa; M. Dhani Arya; M. Rikza Husna Asyrofi (LPPM IAI Almuslim Aceh, 2025)
This research is to analyze and identify the development of science and Islam for human life. This research focuses on understanding the development between Islam and science and attempts to determine the gap between them, emphasizing the importance of balance and harmony between science and religion, and supporting the urgency of paying attention to and studying science and Islam together for the sake of human progress and welfare. Using a literature research design and citing reference sources from journals, scientific articles, and previous research reports, the findings relate to the development of science and Islam for life. This research provides the development of science towards changes related to human life, affecting the way of thinking, lifestyle, and behavior. The development of science has changed the way we view the world and improved the quality of human life through technological innovation and understanding of the universe. While science provides great material benefits, its integration with Islamic views also emphasizes its spiritual relevance.